Business Process Improvement Sistem Pelayanan Klinik Promec Menggunakan Metode Time Motion Study and Value Stream Mapping Untuk Mengurangi End-To-End Lead Times - Fransiska Mochtar; Purwadhi Purwadhi; Nining Handayani (Research of Service Administration Health and Sains Healthys, 2025)
Process efficiency is a key factor in improving the quality of healthcare services, especially in outpatient facilities such as clinics. This study presents a case study at Promec Clinic in Jakarta, aiming to identify bottlenecks and design process improvement recommendations to reduce end-to-end lead time. A descriptive and explanatory quantitative approach was employed, integrating Time and Motion Study (TMS) and Value Stream Mapping (VSM) as primary analysis tools. Data were collected through direct observation of 100 patients, interviews with staff, and operational process satisfaction questionnaires. The results indicate that the "during examination" stage contributes 73.6% of the total service time, while the "before examination" stage is the primary source of operational errors, particularly in form filling (45.59%) and data entry (39.71%). Pareto and Fishbone analyses reveal that manual procedures, lack of standardization, and reliance on informal communication are root causes of inefficiency. Improvement recommendations include digitizing patient forms using a dedicated registration system, implementing self-service kiosks, conducting periodic staff training, and developing Lean-based Standard Operating Procedures (SOPs). These findings offer practical contributions for clinic management in designing more efficient processes and serve as a reference for applying Lean methodologies in primary healthcare settings in Indonesia.